Pentingnya Bahasa Indonesia dalam Membangun Kesadaran Demokrasi di Sekolah pada Mahasiswa/i Jurusan PPKn - Amalia Apriliani; Joya Urmila Lubis; Trima Uasito Tampubolon; Petrus Medikson Pardede; Nurul Azizah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Bahasa Indonesia, as the official language and primary means of communication in Indonesia, not only serves as a link between diverse ethnicities and cultures, but also as an effective medium for conveying democratic values ​​to students. This study uses a qualitative method with a descriptive approach to understand the meaning behind the use of language in learning activities. The results of the study indicate that good mastery of Bahasa Indonesia can facilitate constructive discussions and interactions, support the teaching of democratic values, and create an inclusive learning environment. Through interactive learning strategies, prospective PPKn teachers can instill awareness of the importance of active participation in a democratic society, build mutual respect, and appreciate differences of opinion among students. This study emphasizes the importance of developing Indonesian language competence for prospective teachers as an effort to create a generation that cares and is responsible for national and state life.